Cross-Protective Efficacy of Monovalent Live Influenza B Vaccines against Genetically Different Lineages of B/Victoria and B/Yamagata in Ferrets. (30th August 2018) - Kiseleva, Irina; Krutikova, Elena; Stepanova, Ekaterina; Donina, Svetlana; Pisareva, Maria; Krivitskaya, Vera; Rekstin, Andrey; Sparrow, Erin Grace; Torelli, Guido; Rudenko, Larisa
Abstract : Background. Currently, two genetic lineages of influenza B virus, B/Victoria and B/Yamagata, are cocirculating in humans in various countries. This situation has raised a question regarding the possibility of cross-protection between B components of live attenuated influenza vaccine (LAIV) belonging to different lineages. This study aimed to assess in naïve ferrets the potential protective activity of monovalent B-LAIVs against challenge with homologous and heterologous wild-type (WT) influenza B viruses. Methods. Groups of seronegative female ferrets 5-6 months of age were given one dose of monovalent LAIV based on B/Victoria or B/Yamagata lineage virus. Ferrets were challenged 21 days later with B/Victoria or B/Yamagata WT virus. Ferrets were monitored closely for clinical signs and morbidity outcomes including febrile response, body weight loss, nasal symptoms, and level of activity one week prior to vaccination and for three days following vaccination/challenge. Nasal washes were collected three days after vaccination/challenge. Samples of lung tissue were taken three days after challenge. All samples were analyzed for the presence of challenge virus by culturing in embryonated chicken eggs and real-time polymerase chain reaction. Antibody response to vaccination was assessed by routine hemagglutination inhibition assay and microneutralization test. Results. Vaccination led to intensive production of specific neutralizing and antihemagglutinating antibodies to vaccine virus, protected ferrets from homologous challenge infection, and significantly reduced clinical signs and replication of homologous challenge virus. In contrast, cross-lineage serum antibodies were not detected. However, ferrets vaccinated with monovalent B-LAIV had a significantly lower level of heterologous challenge virus in the respiratory tract than those given challenge virus only. Conclusions. Monovalent B-LAIV has the potential to be cross-protective against infection with genetically different influenza lineages. Further studies are required to confirm this effect.